Confucius Institute at Universitas Al Azhar, Jakarta; The unseen power of China - Lan, Thung Ju (UI Scholars Hub, 2017)
China's soft power is a difficult concept to measure if the Confucius Institute is the only source relied on. Joseph Nye's concept of soft power puts a strong emphasis on